Two-year cortical trajectories are abnormal in children and adolescents with prenatal alcohol exposure. (April 2018) - Hendrickson, Timothy J.; Mueller, Bryon A.; Sowell, Elizabeth R.; Mattson, Sarah N.; Coles, Claire D.; Kable, Julie A.; Jones, Kenneth L.; Boys, Christopher J.; Lee, Susanne; Lim, Kelvin O.; Riley, Edward P.; Wozniak, Jeffrey R.
Abstract: Objectives: Cortical abnormalities in prenatal alcohol exposure (PAE) are known, including in gyrification (LGI), thickness (CT), volume (CV), and surface area (CS). This study provides longitudinal and developmental context to the PAE cortical development literature. Experimental design: Included: 58 children with PAE and 52 controls, ages 6–17 at enrollment, from four Collaborative Initiative on FASD (CIFASD) sites. Participants underwent a formal evaluation of physical anomalies and dysmorphic facial features associated with PAE. MRI data were collected on three platforms (Siemens, GE, and Philips) at four sites. Scans were spaced two years apart. Change in LGI, CT, CS, and CV were examined. Principal observations: Several significant regional age-by-diagnosis linear and quadratic interaction effects in LGI, CT, and CV were found, indicating atypical developmental trajectories in PAE. No significant correlations were observed between cortical measures and IQ. Conclusions: Regional differences were seen longitudinally in CT, CV, and LGI in those with PAE. The findings represent important insights into developmental trajectories and may have implications for the timing of assessments and interventions in this population. It is noteworthy that cortical metrics did not correlate with IQ, suggesting that more specific aspects of cognitive development may need to be explored to provide further context.